Wireless condition monitoring of machinery and equipment in maritime industry : an overview - Panić, Ivan (Array, 2018)
Seagoing vessels are highly complex systems. Major requirements of marine vessels are continuous running time and high production output. As such, these systems require high availability and reliability, and are dependent on preventive maintenance procedures. Development of diverse range of sensors, combined with overall reduction in price, enabled implementation of condition based maintenance in such systems. Large increases in fuel cost, environmental restrictions and further crew reduction are current trend in maritime industry. Considering marine sector emphasis on the reduction of fuel consumption, environmental restrictions, and reduction of crew size, implementation of condition based maintenance is favourable, especially with regard to lost man-hours. However, high initial cost of installation on moving vessels, necessary crew training and additional sensor maintenance inhibits implementation of condition based maintenance. Replacing wired monitoring system with wireless ship-board sensor network would mitigate the above mentioned problems. However, current research of wireless sensor networks is based on terrestrial installation. This paper analyses the application of wireless sensor network technology on board seagoing vessels. Practical engineering solutions, including sensor types, configurations and wireless network topologies have been identified and reviewed.